Laryngeal tuberculosis and stridor in a patient with AIDS - Buff, Daniel D.; Frazão, João M.; Grochowski, Sabrina (Portuguese Journal Internal Medicine, 1995)
We present thefirst reported case ofrespiratory distress and stridor due laryngeal tuberculosis to occur in a patient with the Acquired Immunodeficiency Syndrome (AIDS). As such, larygeal tuberculosis should considered as a possible cause when an AIDS patient develops respiratory distress.